The Monitoring System of Air Pressure Difference inside Clean Room in Semi Solid Building in Real-Time System (International Journal of Psychosocial Rehabilitation, 2020)
The setting of the air pressure difference for each room in industrial world had the most important role, especially that was working in food and pharmaceutical production. In food and pharmaceutical production had to follow the regulation such as BPOM (The National Food and Drug Agency). The pressure difference in each room had an important role so that it could not become cross contamination among the room. It would be affected to the quality of food and drug product which taken be produced. Therefore, it would be needed a system which could monitor the pressure difference in real-time system in production room. In this research we used Zelio Smart Relay SR3B261FU which was programmed to control the pressure difference in real-time so it could not occur cross contamination. The purpose of this research has been expected able to help data collection more efficient to monitor about 90% in time and could increase the operator response and supervision for the air pressure which was happened in production area.